WEB-BASED EXPERT SYSTEM APPLICATION TO RECOMMEND COMPUTER SPECIFICATIONS FOR GAMING USING BACKWARD CHAINING INFERENCE METHOD - Gottfried Christophorus Prasetyadi; Mahfudin Mahfudin (Faculty of Computer Science Universitas Indonesia, 2017)
This study aims to design and implement an expert system application to provide minimum computer hardware and operating system requirements, which are capable of running games with certain graphical settings. Backward chaining inference method is used to conclude the output, which the requirements are based on user’s input. The application is made using PHP general-purpose server-side scripting language and MySQL database. By using this application, a user can consult as well as to an expert to know the computer specifications capable of running a game with preferred graphical settings and to estimate the cost to build that computer. This application can also help sellers of computer parts to set price on the custom-built computers, to create category or sales package, as well as to provide information for potential buyers.